Pengaruh Pemberian Teh Hitam terhadap VO2max dan Pemulihan Denyut Nadi Pasca Melakukan Latihan Treadmill (The Effect of Black Tea on VO2max and Heart Rate Recovery Time after Treadmill Exercise) - Yedi Murdanu; Cholis Abrori; Muhamad Hasan (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
In sports, caffeine is oftenly consumed as a stimulant in intense exercise. Caffeine consists in black tea with the content is about one third to eighth compared to black coffee, The aim of this research was to find out the effect of black tea to VO2max and heart rate recovery time after treadmill exercise. There were 2 groups. Control group which consumed placebo and treatment group which consumed black tea. Both group performed Bruce Treadmill Test Protocol. The results showed that the mean value of VO2max were 32,525 for control group and 38,442 for treatment group. Data analysis using T-paired test showed that treatment group had significantly higher VO2max value than control group (p=0,0001). Heart rate change data showed that heart rate frequency in treatment group from every fixed time was higher than the control group The heart rate recovery time was 59 minutes for control group and 66 minutes for treatment group. In conclusion, consumption of black tea before exercise would increase VO2max value and extend the heart rate recovery time. Keywords: Black tea, VO2max, heart rate recovery, Bruce treadmill test protocol